Control of Human Immunodeficiency Virus Type 1 RNA Metabolism: Role of Splice Sites and Intron Sequences in Unspliced Viral RNA Subcellular Distribution - Séguin, Béatrice (American Society for Microbiology, 1998)
In the course of examining the various factors which affect the metabolism of human immunodeficiency virus type 1 (HIV-1) RNA, we examined the role of intron sequences and splice sites in determining the subcellular distribution of the RNA. Using in situ hybridization, we demonstrated that in the absence of Rev, unspliced RNA generated with an HIV-1 env expression construct displayed discrete localization in the nucleus, coincident with the location of the gene and not associated with SC35-containing nuclear speckles. Expression of Rev resulted in a disperse signal for the unspliced RNA throughout both the nucleus and the cytoplasm. Subsequent fractionation of the nucleus revealed that the majority of unspliced viral RNA within the nucleus is associated with the nuclear matrix and that upon expression of Rev, a small proportion of the unspliced RNA is found within the nucleoplasm. Mutations which altered splice site utilization did not alter the sequestration of unspliced RNA into discrete nuclear regions. In contrast, a 2.2-kb deletion of intron sequence resulted in a shift from discrete regions within the nucleus to a disperse signal throughout the cell, indicating that intron sequences, and not just splice sites, are required for the observed nuclear sequestration of unspliced viral RNA.